PENGARUH SHOPPING LIFE STYLE DAN FASHION INVOLVEMENT TERHADAP IMPULSE BUYING BEHAVIOR MASYARAKAT HIGH INCOME SURABAYA - Edwin Japarianto; Sugiono Sugiharto (Institute of Research and Community Outreach - Petra Christian University, 2011)
Dynamics of the retailing business economy in Indonesia develop rapidly, so that it triggers the customers’ shopping lifestyle and their fashion involvement as well. They have higher expectation, demand more and desire better quality product consistently. But in the other side there are some problems. For instance the prosperity consumers spend their money fluctuatively and oftenly out their financial plan. The purpose of this research is proving, whether shopping lifestyle and fashion involvement will influence the impulse buying behavior of Surabaya’s high income community. As sampling, this study used the population of Surabaya that usually spend their money more or equal to Rp.1.250.000 per month, and ever go shopping at Galaxy mall, Lendmarc and Grand City. The technical analysis to examining the role of shopping lifestyle and fashion involvement toward the impulse buying behavior is Multi linear Regression. The examination result showed that Hedonic Shopping Value and Fashion Involvement influenced the Impulse Buying Behavior of Surabaya’s High Income Society.